Nonlinear Optical and Atomic Systems At the Interface of Physics and Mathematics - Besse, Christophe; Garreau, Jean-Claude (Lecture Notes in Mathematics, 2015)
Focusing on the interface between mathematics and physics, this book offers an introduction to the physics, the mathematics, and the numerical simulation of nonlinear systems in optics and atomic physics. The text covers a wide spectrum of current research on the subject, which is  an extremely active field in physics and mathematical physics, with a very broad range of implications, both for fundamental science and technological applications: light propagation in microstructured optical fibers, Bose-Einstein condensates, disordered systems, and the newly emerging field of nonlinear quantum mechanics.   Accessible to PhD students, this book will also be of interest to post-doctoral researchers and seasoned academics.